2018
DOI: 10.1159/000496047
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent-Hypoxia-Induced Autophagy Activation Through the ER-Stress-Related PERK/eIF2α/ATF4 Pathway is a Protective Response to Pancreatic β-Cell Apoptosis

Abstract: Background/Aims: Intermittent hypoxia (IH) causes apoptosis in pancreatic β-cells, but the potential mechanisms remain unclear. Endoplasmic reticulum (ER) stress, autophagy, and apoptosis are interlocked in an extensive crosstalk. Thus, this study aimed to investigate the contributions of ER stress and autophagy to IH-induced pancreatic β-cell apoptosis. Methods: We established animal and cell models of IH, and then inhibited autophagy and ER stress by pharmacology and small interfering RNA (siRNA) in INS-1 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 44 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…In addition, caspases were activated in the process of apoptosis [19]. Autophagy is also a type of cell death which degrades and recycles long-lived or damaged proteins and cytoplasmic organelles by lysosomes [20]. During autophagy, p62 protein is degraded while LC3-I is converted to LC3-II [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, caspases were activated in the process of apoptosis [19]. Autophagy is also a type of cell death which degrades and recycles long-lived or damaged proteins and cytoplasmic organelles by lysosomes [20]. During autophagy, p62 protein is degraded while LC3-I is converted to LC3-II [21].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, from our previous study, we did not observe ER stress activation in the hippocampus after 7 days of IH treatment, but was significantly activated after 14 days of IH treatment [8]. Also, it has been reported that PERK-elf2-ATF-4 arm is activated to induce apoptosis in prolonged IH treatment [30]. Caspase-12 has been proposed as a key mediator under the execution phase of ER stressinduced apoptosis, with its activation by means of excessive ER stress and in turn activating pro-caspase-3, leading to apoptosis [31].…”
Section: Discussionmentioning
confidence: 59%
“…In this study, we proved that ATF4-mediated autophagy activation plays a crucial role in IL-22 protecting hepatocytes against LPS-induced damage. Previous investigations described that intermittent hypoxia induced autophagy activation is dependent on PERK/eIF2α/ ATF4 signaling pathway, inhibition of autophagy by chloroquine or deficiency of autophagy-related gene 5 (Atg5) and Atg7 promoted pancreatic β-cell apoptosis 36 . In addition, ATF4 depletion promotes hepatocytes apoptosis by inhibiting autophagy 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations described that intermittent hypoxia induced autophagy activation is dependent on PERK/eIF2α/ ATF4 signaling pathway, inhibition of autophagy by chloroquine or deficiency of autophagy-related gene 5 (Atg5) and Atg7 promoted pancreatic β-cell apoptosis 36 . In addition, ATF4 depletion promotes hepatocytes apoptosis by inhibiting autophagy 36,37 . Collectively, our study suggests that ATF4 is an essential downstream molecule of IL-22-activated autophagy in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%